Active species evolution in the presence of different targets impacted by a helium plasma jet at atmospheric pressure. (4th January 2022) - Cosimi, J; Merbahi, N; Marchal, F; Eichwald, O; Yousfi, M
Abstract: A low-temperature plasmas jet is generated by a dielectric barrier discharge powered by a pulsed high voltage in helium flow (3 L min −1 ) at atmospheric pressure in the presence of different targets (a glass slide, ultra-pure water and a grounded metal plate) positioned perpendicular to the plasma propagation axis. Experimental electrical characterizations such as discharge current, voltage and power, and optical characterizations such as intensified camera ICCD, Schlieren imaging and emission spectroscopy to follow specific excited species have been achieved. The transition from laminar to turbulent regime was observed during the discharge ignition with a larger spreading of the plasma on the surface target with lower dielectric permittivity. The generation of two discharges during each voltage pulse is highlighted during the propagation of the ionization wave which has a variable speed along the plasma axis not depending on the target kind. The evolution of some active species (such as OH, O and excited nitrogen and helium) are investigated using time resolved mapping of the emissions of radiative excited species propagating in ambient air between the plasma jet output and the target. For a low relative permittivity target (glass), the volume ionization wave at its arrival on the target spreads on its surface thus behaving as a surface ionization wave. For the highest relative permittivity (metal), a conductive channel appears between the target surface and the plasma jet during the first discharge, followed by a diffuse plasma plume from the target surface towards the plasma jet after the impact of the ionization wave on the target. A hybrid behavior is highlighted for the ultra-pure water which leads to a short spreading of the ionization wave on the target surface, the formation of a conductive channel in ambient air between tube output and target and the formation of a plasma plume on the target surface.